Ekosistem Manajemen Talenta Dalam Pengelolaan Pengembangan ASN yang Profesional di Kota Bima - Miftahuddin Miftahuddin; Ridwan Ridwan; Musmuliadin Musmuliadin (Jayapangus Press, 2026)
The implementation of talent management is a juridical-strategic instrument to manifest a meritocracy system aimed at achieving the professionalism of the Civil Service Apparatus (ASN). This study aims to analyze regulatory readiness and the institutional policy design of the talent management ecosystem in developing a professional Civil Service Apparatus in Bima City. The research method used is empirical legal research (socio-juridical) focused on the Regional Civil Service and Human Resources Development Agency (BKPSDM) of Bima City. Data collection was conducted through in-depth interviews with key bureaucratic actors, observations, and a study of civil service legal documents. The research findings indicate that as an initial achievement, the Bima City Government has laid the foundation for the merit system, earning a